(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
This article demonstrates that the category of unreliable narration can be fruitfully applied to both narrative fiction and film. Taking as its starting point Wayne Booth’s canonical definition of the narrative technique in question,the first part of the article identifies two major strands in narratological research into unreliable narration: rhetorical, represented by James Phelan, and cognitive, developed by Ansgar Nünning. The major aspects of their respective conceptualisations are juxtaposed with examples adduced from narrative fiction in English, with particular attention being paid to problematic elements in their understanding of this literary technique. The second part of the article discusses, in turn, unreliable narration in film. Such devices as voice-over, frame narrative and multiple points of view can indicate that a perspective from which a particular sequence of events is presented cannot be trusted and thus endow a particular film with qualities of unreliable narration. Taken together, the novelistic and filmic instances discussed in this article demonstrate relevance of this narrative device for contemporary culture.